SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB - Sukirno Sukirno (IAIN Ponorogo, 2013)
Today the development of science and technology is dinamic, even faster than before, one of it is the existence of internet. Web is the collection of pages used to show information, motion pictures, audio, audio visual, both static or dinamic. Web can be used for information management system. The use of it will spread information dissemination and promotion of library to the users of Indonesian or abroad. So the library must optimize web as information system to achieve the purposeof library.